Algorithm development for optimization of a refrigeration system - Izzat, Mohamad Adnan (2010)
This thesis deals with algorithm development for optimization of a refrigeration system. As the refrigeration system has become one of the basic needs to us, the actual working principle is essential to be known by us so that we can always optimize the system performance and minimize the resources used. Objectives of this thesis to find an algorithm and optimum charge by pressure for refrigeration system. The thesis describes the step by step the method to find an algorithm by using experimental data. Vapor compression refrigeration system was studied as it is the most widely used refrigeration system especially in small scale of refrigeration application such as in domestic application. An experiment was conducted to find temperature and pressure at point interest. Finally, obtained the enthalpies for each of the points of interest by using conventional method using P-h diagram based on combination of temperature and pressure data taken from experiment from the value of enthalpies ateach point of interest, performance analysis was conducted to obtain the compressor work, heat picked up, and the COP From the result we use Statistica software to generate an algorithm and by the algorithm find the optimum charge for refrigerator system based on international COPR . R. Based on result show that decrease the pressure charge to the system will increase the cooling effect and the COP but will decrease the compressor work and the heat rejected by refrigerator system. By using the Statistica software the new algorithm was generate by using linear regression analysis and the algorithm defined as γ = 4.284109 - 0.057164 χR from the algorithm and the international domestic refrigerator using R-134a COP value, was showed that the optimum charge for the refrigerator system occur at 31.21psi.R